The assertion of playfulness in the science textbooks for the early years of elementary school - Ferreira, Mariane Grando; Shigunov Neto, Alexandre; Strieder, Dulce Maria (Revista Hipótese, 2022)
The construction of scientific knowledge in the Early Years can contribute to the criticality and active participation of students in society. Therefore, among the countless elements under discussion in Science Teaching for the Early Years, one is related to stimulating the student's action, being in this context the playful one of great value. This article aims to discuss the role of the use of playfulness in the directions of the Textbook of Natural Sciences for the Early Years, based on a bibliographic and documentary research on the subject. As a result, we describe the importance of the use of play being present even as a criterion for the selection of Science Textbooks and we point to alternatives for action.
Keywords: Science teaching; Playful; Textbook; Early Years